The question of Identity between the restorative and regenerative organ transplantations - Shogar, Ibrahim; Mohd Yusof, Nazri; Mohamad Yussoff, Mohamad Ariff; Mat Din, Mohd. Azid; Abdullah Ripain, Iswatun Hasanah; Hashim, Iffah Inani; Mohd. Yusof, Fatihah (Kulliyyah of Science, International Islamic University Malaysia (IIUM, and Malaysian Analytical Science Society (ANALIS), 2018)
This paper explores implications of organ transplantation on identity and body integrity. It investigates how advancements in transplant technologies can affect and reshape our conception of identity at individual and social levels. The question of identity as a distinctive code for every organism is increasingly becoming important due to the advanced biomedical technologies and its legal, ethical, and social implications. Modes of organ transplantation, in this paper are divided into two major types (i) restorative and (ii) regenerative. Both types have important implications on conception of identity, at various levels, from both biological and social perspectives. While highlighting all these dimensions, this article focuses on implications of restorative organ transplantation on identity based on four specific cases, which are: (i) hand transplantation, (ii) facial transplantation, (iii) reproductive organ transplantation, and (iv) head / body transplantation. Investigating all these cases, the paper has concluded that while the advanced biomedical technology is essential for survival of many lives, application of such technologies must be consistent with moral values and the universal principles for human dignity and body integrity.